Formal Diversity and the Philosophy of the Unit Design Decorative Architectural Formations - Abdulhameed Majeed, Oday (Opción, 2019)
The research problem was a fundamental question: What is the formal diversity in the unit of decorative architectural forma- tions? The research aims to answer the question in the problem as the research is determined by the geometric decoration and variations of the formality within the unit of formation on the facades of architecture in Baghdad in (1 42 H-14 40 e) (7 60 m - 20 19 m) The importance of research is: 1. Reveals the artistic and design foundations employed in geometric decorative formations. 2. Con- tributes to the awareness of the intellectual and practical aspects of students of the Faculty of Fine Arts, especially the Department of Arabic calligraphy and decoration design students. 3. The Department of Architectural Decorates works in the Faculty of Engineering, Design and Architectural Design at the Institute of Applied Arts. The theoretical framework deals with the following topics: a historical introduction about the emergence of the decoration and its mathematical relations, the geometric shapes in the buildings, as well as the conceptual-visual elements of the geometric form, as well as the relational elements and geometrical transformations, including the spatial relationship in the geometric shape. The researcher followed in his procedures descriptive analytical approach to achieve the results of achieving its objectives and solve the problem and the sample was selected in an intentional manner, where the number of samples (3) sample of the total (24) model. And design the tool (form) and presented to the experts to verify their validity, and achieve the objectives. The re- search reached results, including: 1. The geometric ornamentation in the base class depends on the construction of the basic network in the light of the available space and according to the variations of repetition, harmo- ny and balance in the drawing of units and decorative vocabulary or the distribution of centers that generate the decorative element in the design center or on the side. 2. The architectural and architectural decoration has a mathematical structure. Mathematics is a logical system and layout in the formations of geometric ornaments in Islamic architecture if decoration is a complete form of mathematical thought. The researcher recommend- ed to benefit from his findings and vocabulary in enhancing and activat- ing the curriculum of engineering decoration in general, in the relevant departments within the faculties and technical institutes. The researcher proposed a study of the aesthetic characteristics of architectural forms and patterns in modern Islamic architecture in Iraq.